Pengaruh Professional Training, Pasar Kerja, Lingkungan Kerja dan Personalitas Terhadap Minat Mahasiswa Akuntansi Unisma Pada Profesi Akuntan Publik - Muhammad Ikhsan Arief Nugraha; M. Cholid Mawardi; Siti Aminah Anwar (Universitas Islam Malang, 2023)
This study aims to find out how and to what extent professional training, job market, work environment and personality influence the interest of accounting students in the public accounting profession. The population in this study were students majoring in accounting at the Malang Islamic University class of 2018, totaling 291 people and the sample in this study using the slovin formula obtained a sample of 74. The test was carried out using IBM SPSS version 26. The results obtained were professional training, job market, work environment and personality simultaneously have a positive and significant effect on students' interest in the public accounting profession. In the mean time, to some extent proficient preparation affects understudies' revenue in the public bookkeeping calling, the work market affects understudies' revenue in the public bookkeeping calling, the workplace affects understudies' revenue in the public bookkeeping calling, character significantly affects understudies' revenue in the public bookkeeping calling.Keywords: Professional training, job market, work environment, personality, student interests.